2001
DOI: 10.1098/rspb.2001.1592
|View full text |Cite
|
Sign up to set email alerts
|

Global warming and body mass decline in Israeli passerine birds

Abstract: Global warming may a¡ect the physiology, distributions, phenology and adaptations of plants and animals. In Israel, minimum summer temperatures increased by an average of 0.26 8C per decade during the second half of the 20th century. Bergmann's rule predicts that, in warm-blooded animals, races from warm regions are smaller than races from cold regions. Numerous studies have reported general correlations between body mass in fossil animals and independently established palaeoclimatic changes from various parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
129
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 24 publications
10
129
6
1
Order By: Relevance
“…In contrast to Allen's rule, however, other studies have noted a decline in tarsus length with increasing temperatures (Yom-Tov 2001;Teplitsky et al 2008).…”
Section: Temporal Changes In Body Size Traitsmentioning
confidence: 44%
“…In contrast to Allen's rule, however, other studies have noted a decline in tarsus length with increasing temperatures (Yom-Tov 2001;Teplitsky et al 2008).…”
Section: Temporal Changes In Body Size Traitsmentioning
confidence: 44%
“…Increase in mean body size at the population level has been demonstrated in some species Yom-Tov 2004, 2005;Yom-Tov et al 2008; review in Millien et al 2006), though the opposite has also been reported (e.g. Smith et al 1998;Yom-Tov 2001;Yom-Tov et al 2006a). Increased body mass has been reported in wild bird populations, probably a combined effect of greater food availability and lower energy demands (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…This is because egg size is only one of the traits that may be affected by climate warming (Both and Visser, 2005), among many others that may be phenotypically and genetically correlated with it (e.g. individual size or condition; see Potti, 1993;Smith et al, 1993;Williams, 1994;Christians, 2002;Yom-Tov, 2001;Lifjeld et al, 2005). Furthermore, adjustment of egg size to changes in environmental phenology, if any, will depend to a certain degree on a previous adjustment of bird phenology to the phenology of the changing environment.…”
Section: Introductionmentioning
confidence: 99%